Perforated duodenal diverticulum. Case Report - Armand Ugon, Gustavo; González, Daniel; Arciénega, Pilar; Rodríguez, Gabriela (Cirugía del Uruguay, 2019)
The perforation of a duodenal diverticulum (Dd) is an exceptional complication, it does not present a pathognomonic clinic. 60-years-old woman, with no history of ulcerative dyspepsia. Intense epigastric pain, transfixing, 8 hours of evolution. Pain on palpation of right hypochondrium. Humoral paraclinical: leukocytosis 14,200, normal rest. Tomography: perforated Dd and retro-peritonitis. Supraumbilical medium. Decodeduodenum-cephalo-pancreatic, identification and resection of theDd, duodenal raffia in two planes (polyglactin-910, surjet), toilette and retroperitoneal drainage. Postoperative: evolution without complications, discharge a week. We solved the perforation by duodenorraphy, we did not perform duodenal exclusion orgastro-jejunum-anastomosis (the latter two are included in the most recommended treatment).